2023
DOI: 10.1002/cctc.202300328
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Water Oxidation by Hydrolytically Stable Metal‐Organic Frameworks at Both Neutral and Alkaline Medium: Inverse Relation of Dimensionality with Catalytic Activity

Abstract: Catalyst development for water splitting to afford hydrogen as a green source of energy is one of the major areas of research in the pursuit of sustainable energy technology solution. Herein, the electrocatalytic water oxidation behaviour of two different Co‐pdc (H2pdc=pyridine‐2,5‐dicarboxylic acid) based metal‐organic frameworks (MOFs) of different dimensionalities (2D and 1D) is reported. 2D‐MOF {[Co(pdc)(H2O)2] ⋅ H2O}n acts as the mother which transforms into daughter 1D‐MOF {[Co(pdc)(H2O)2] ⋅ 7H2O}n via c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(118 reference statements)
0
2
0
Order By: Relevance
“…At neutral pH, the OER overpotentials are 0.77 and 0.46 mV for the 2D and 1D MOFs, respectively, for a current density of 1 mA cm –2 . These values reduce to 0.36 and 0.25 mV at pH = 14 . Yang et al have reported OER activity of MIL-53­(Fe)-2OH at an overpotential of 215 mV with a current density of 10 mA cm –2 in 1 M KOH .…”
Section: Applications Of Conducting Mofsmentioning
confidence: 98%
See 1 more Smart Citation
“…At neutral pH, the OER overpotentials are 0.77 and 0.46 mV for the 2D and 1D MOFs, respectively, for a current density of 1 mA cm –2 . These values reduce to 0.36 and 0.25 mV at pH = 14 . Yang et al have reported OER activity of MIL-53­(Fe)-2OH at an overpotential of 215 mV with a current density of 10 mA cm –2 in 1 M KOH .…”
Section: Applications Of Conducting Mofsmentioning
confidence: 98%
“…These values reduce to 0.36 and 0.25 mV at pH = 14. 194 Yang et al have reported OER activity of MIL-53(Fe)-2OH at an overpotential of 215 mV with a current density of 10 mA cm −2 in 1 M KOH. 195 Tang et al have shown electrocatalytic OER activity of ultrathin nanosheets of 2D NiCo-UMOFN at an overpotential of 180 mV with a current density of 10 mA cm −2 in 1 M KOH.…”
Section: Applications Of Conducting Mofsmentioning
confidence: 99%